Тюркизмы в рaзных языкaх мирa (Вестник КазНУ. Серия Востоковедения, 2018)
The languages of the Turkic peoples left many traces in a variety of languages. This article examinesthe Turkism in different languages of the world. Achieving the goal determines the need to solve the followingtasks: to consider the main ways of borrowing and the concept of “Turkism”, to study the Turkismin the “Lay of Igor’s Campaign,” to analyze the conditions and ways of penetrating the Turkism into Russian;to consider the peculiarities of Russian names of Turkic origin.